2009
DOI: 10.1117/1.3210779
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of neural-hemodynamic coupling to alterations in cerebral blood flow during hypercapnia

Abstract: The relationship between measurements of cerebral blood oxygenation and neuronal activity is highly complex and depends on both neurovascular and neurometabolic biological coupling. While measurements of blood oxygenation changes via optical and MRI techniques have been developed to map functional brain activity, there is evidence that the specific characteristics of these signals are sensitive to the underlying vascular physiology and structure of the brain. Since baseline blood flow and oxygen saturation may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
4
26
1
Order By: Relevance
“…Thus, hypoxia and hypercapnia alter cerebral autoregulation, and both states likely contribute to the pathogenesis of cardiovascular and cerebrovascular disease in patients with OSAS. 10 This is supported by recent observations that neural activity changes are sensitive to hypercapnia-induced alterations in baseline cerebral blood flow, 20,21 and that hypercapnia-induced perfusion changes are closely associated with impairments in learning and memory. 22 Notably, former studies indicate that impaired vasomotor reactivity can be reversed relatively rapidly when nightly exposure to intermittent hypoxia is eliminated with continuous positive airway pressure in patients with OSAS.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, hypoxia and hypercapnia alter cerebral autoregulation, and both states likely contribute to the pathogenesis of cardiovascular and cerebrovascular disease in patients with OSAS. 10 This is supported by recent observations that neural activity changes are sensitive to hypercapnia-induced alterations in baseline cerebral blood flow, 20,21 and that hypercapnia-induced perfusion changes are closely associated with impairments in learning and memory. 22 Notably, former studies indicate that impaired vasomotor reactivity can be reversed relatively rapidly when nightly exposure to intermittent hypoxia is eliminated with continuous positive airway pressure in patients with OSAS.…”
Section: Discussionsupporting
confidence: 67%
“…This is higher than values reported in the literature for capillaries saturation S cO2 of about 70% (Mesquita et al, 2009;Huppert et al, 2009). We tried fixing the value of S wO2 to literature values, but the constrained model would not fit our experimental data.…”
Section: Estimate Of Baseline Oxygen Saturation S Wo2contrasting
confidence: 51%
“…Though it may be difficult to separate non-linear neuronal effects from vascular response nonlinearities, a recent study showed that hemodynamic nonlinearities do affect BOLD fMRI response timing and magnitude, and that, "if not properly taken into account such vascular nonlinearities confound the interpretation of underlying neuronal events" (de Zwart et al, 2009). Moreover, the fact that the absolute changes in blood flow, rather than the normalized (percent) changes, are most closely coupled to neural activity across normal and hypercapnic conditions (Huppert et al, 2009) might be at least partially interpreted through the biomechanical mechanisms pointed out in the present study.…”
Section: Hemodynamic Variations Induced By Global Vasodilationsmentioning
confidence: 99%